The Influence of Work Discipline and Organizational Commitment on Employee Performance at PT Bank SulutGo Tomohon Branch - tulung, Even (JURNAL ADMINISTRASI BISNIS, 2025)
This study aims to analyze the influence of Work Discipline and Organizational Commitment on Employee Performance at PT Bank Sulutgo Tomohon Branch. This study uses a quantitative approach with a focus on employees as a population. The sample was selected using simple random sampling technique, involving a total of 53 respondents. Data analysis was carried out using the R test, F test, convergent validity, and path coefficient test. The results of this study indicate that Work Discipline has a strong and significant influence on Organizational Commitment with a coefficient value of 0.685 (P < 0.05), which means that the higher the work discipline of employees, the higher their commitment to the organization. In addition, Work Discipline is also proven to have a very strong influence on Employee Performance with a coefficient value of 0.804 (P < 0.05), which indicates that improving work discipline contributes significantly to improving employee performance. However, the results of this study also reveal that Organizational Commitment does not have a significant effect on Employee Performance, with a coefficient value of 0.104 (P > 0.05), which indicates that other factors may be more instrumental in determining employee performance.